1976
DOI: 10.1090/s0002-9947-1976-0412112-8
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Kloosterman sums and the Fourier coefficients of cusp forms

Abstract: ABSTRACT. Certain generalized Kloosterman sums connected with congruence subgroups of the modular group and suitably restricted multiplier systems of half-integral degree are studied. Then a Fourier coefficient estimate is obtained for cusp forms of half-integral degree on congruence subgroups of the modular group and the Hecke groups G(\/2) and G(\/T).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…By way of contradiction, we assume that Xr is a congruence character. In [4] it is shown that any congruence character on a congruence subgroup of level n is identically one on F(48n2) when m = 2 and F(36n2) when tn 3 …”
Section: Xr (M) = Exp [Git(i -N)(bd + Ac/n)/m] Exp[ 7{(n -1)(m + 1)(amentioning
confidence: 99%
“…By way of contradiction, we assume that Xr is a congruence character. In [4] it is shown that any congruence character on a congruence subgroup of level n is identically one on F(48n2) when m = 2 and F(36n2) when tn 3 …”
Section: Xr (M) = Exp [Git(i -N)(bd + Ac/n)/m] Exp[ 7{(n -1)(m + 1)(amentioning
confidence: 99%
“…These two groups are the only Hecke groups, aside from the modular group, whose elements are completely known (see Remark 3.2). Also, H q is commensurable with SL(2, Z) if and only if q = 3, 4 or 6 (see [14,19,20,27]). We will consider the group H 4 at the end of Section 3.…”
Section: Introductionmentioning
confidence: 99%
“…This estimate is a considerable improvement upon Hecke's [29,Satz 8], [30, p. 484] well-known estimate a(n) = O(n k/2 ) for the Fourier coefficients of f . Note that Weil's bound for Kloosterman sums [114] implies that a(n) = O (n k/2−1/4+ ) for any > 0 (see L. A. Parson's paper [47] for conditions on f ensuring this bound), while the celebrated theorem of Deligne [19], proving the Ramanujan-Petersson conjecture, asserts that a(n) = O (n k/2−1/2+ ) ( > 0) on subgroups Γ 0 (N ), where k is any positive integer, and the multiplier system is any Dirichlet character modulo N . The latter estimate, by the way, is best possible as was demonstrated in another paper by Rankin [84].…”
Section: Rankin-cohen Brackets and Differential Operators On Modular mentioning
confidence: 99%